The relationship between polymorphisms in intron 8 of vitamin D receptor gene and occult HBV infection - Rezvani ME (Tehran University Medical Journal, 2009)
"n Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 Background: Occult hepatitis B infection (OBI) is a form of hepatitis in which despite absence of detectable HBsAg, HBV-DNA is present in peripheral blood of patients. The responsible mechanisms for progression of OBI yet to be clarified, but some investigators believed that the genetics and immunological parameters are different in resistant individuals and patients. Vitamin D3 and its receptor interaction could be involved in anti-viral immune response. The aim of this study was to investigate the association between polymorphisms in intron 8 of VDR with OBI."n"n Methods: In this experimental study, the plasma samples of 3700 blood donors were collected and tested for HBsAg and anti-HBs by ELISA. The HBsAg negative and anti-HBc positive samples were selected and screened for HBV-DNA using PCR. HBV-DNA positive samples were assigned as OBI cases and PCR-RFLP was performed to examine the polymorphisms in intron 8 of VDR genes."n"n Results: Results of current study indicated that 352 (9.5%) of 3700 blood samples were HBsAg- and anti-HBc+. HBV-DNA was detected in 57/352 (16.1%) of HBsAg- and anti-HBc+ samples. Our results showed that no significant difference was observed in Apa-1 polymorphisms of intron 8 of VDR and OBI patients."n"n Conclusion: Our results demonstrated that there are not any association between Apa-1 detected alleles and OBI, hence, it can be concluded that these alleles are not associated with OBI and other researchers should evaluate relation between other polymorphisms of VDR with OBI.